Vestibular Deficits Following Concussion - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from the Division of Emergency Medicine, Sports Medicine, and Department of Pediatrics, Children's Hospital of Philadelphia, PA, and Sports Medicine, Somerset, NJ, performed a retrospective cohort study of 247 patients ages 5-18 years with concussion referred from July 2010 to Dec 2011; 81% of patients showed a vestibular abnormality on initial clinical examination.